2020
DOI: 10.1101/2020.02.28.20028068
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiological and clinical features of COVID-19 patients with and without pneumonia in Beijing, China

Abstract: Background: SARS-CoV-2-caused coronavirus disease (COVID-19) is posing a large casualty. The features of COVID-19 patients with and without pneumonia, SARS-CoV-2 transmissibility in asymptomatic carriers, and factors predicting disease progression remain unknown. Methods: We collected information on clinical characteristics, exposure history, and laboratory examinations of all laboratory-confirmed COVID-19 patients admitted to PLA General Hospital. Cox regression analysis was applied to identify prognostic fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 29 publications
6
70
2
Order By: Relevance
“…Different methods, different specimens (serum or plasma) and the different classi cation of disease severity could explain this heterogeneity. However, the highest concentrations of IL-6 are always in association with severe disease [3,5,27,28], which is in line with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Different methods, different specimens (serum or plasma) and the different classi cation of disease severity could explain this heterogeneity. However, the highest concentrations of IL-6 are always in association with severe disease [3,5,27,28], which is in line with our results.…”
Section: Discussionsupporting
confidence: 92%
“…This compassionate-use program was initiated to understand the feasibility of suppressing CRP production with siltuximab and improving the outcomes in patients with COVID-19 requiring CPAP or NIV for pneumonia/ARDS treatment. Initial evidence from China where the first cases of COVID-19 emerged, indicate that excessive production inflammatory markers, such as IL-6 and CRP, correlate with severity of disease (Chen X et al 2020;Conti P et al 2020;Diao B et al 2020;Gong J et al 2020;Liu et al 2020;Yang et al 2020), and many more studies report a significant increase in IL-6 or CRP levels in patients with severe or critical COVID-19 compared with those patients with mild disease (Cai et al 2020;Chen J et al 2020;Feng C et al 2020;Huang Y et al 2020;Liu J et al 2020;Qin C et al 2020;Ruan Q et al 2020;Shi Y et al 2020;Wang Y et al 2020;Wang Z et al 2020;Wu C et al2020;Xu W et al 2020;Xu X et al 2020;Zeng Q et al 2020;Zhao Z et al 2020;Zhang B et al 2020;Zhou F et al 2020;Zhou Y et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Although most cases were mild to moderate, some patients developed severe symptoms characterized by respiratory dysfunction and/or multiple organ failure [3]. In the current situation, identification of COVID-19 disease progression mainly relies on the clinical manifestation, while no effective biomarker has been proposed.…”
Section: Disponible En Ligne Surmentioning
confidence: 99%
“…We initially identified 73 articles based on our search strategy, 64 of which were excluded after title, abstract, or full-text reading, because they were review articles, did not report IL-6 levels, or did not classify the condition of COVID-19 patients as non-severe and severe. Finally, only nine studies were included in this meta-analysis [1][2][3][4][5][6][7][8][9]. Although the heterogeneity was considerably high (I 2 = 89%; P < 0.00001), we observed that IL-6 levels were significantly increased in COVID-19-infected patients with severe condition compared with those with non-severe condition (SMD = 0.71, 95%CI −0.31-1.12, P = 0.0005) ( Fig.…”
Section: Disponible En Ligne Surmentioning
confidence: 99%